The basis and sustainability of the new growth model of the Chinese economy - Antevski Miroslav (Međunarodni Problemi, 2013)
The Chinese model of economic growth has produced impressive results in the past several decades, while the rates of economic growth and exports and imports growth have been the highest in the world. It has been based on cheap money, cheap labour and resources, while the investment basis has been high rates of reinvestment profits. The most dynamic sector of the Chinese manufacturing exports has been processing trade. For this reason, it is called export-led growth model. The new model, which was announced in 2011, should result in some change of the main driving forces of exports growth - apart from investments and exports, consumption should play a significant role. In this way, growth would be driven by a combined impact of primary, secondary and tertiary sectors, by stimulating of domestic consumption, improvement of investment mix, further industrialisation, urbanisation and modernisation of agriculture. [Projekat Ministarstva nauke Republike Srbije, br. 179029: Srbija u savremenim međunarodnim odnosima: Strateški pravci razvoja i učvršćivanja položaja Srbije i međunarodnim integrativnim procesima - spoljnopolitički, međunarodni ekonomski, pravni i bezbednosni aspekti]